2003
DOI: 10.1073/pnas.1633513100
|View full text |Cite
|
Sign up to set email alerts
|

Profiling receptor tyrosine kinase activation by using Ab microarrays

Abstract: Signal transduction in mammalian cells is mediated by complex networks of interacting proteins. Understanding these networks at a circuit level requires devices to measure the amounts and activities of multiple proteins in a rapid and accurate manner. Ab microarrays have previously been applied to the quantification of labeled recombinant proteins and proteins in serum. The development of methods to analyze intracellular signaling molecules on microarrays would make Ab arrays widely useful in systems biology. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
120
0
2

Year Published

2005
2005
2010
2010

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(125 citation statements)
references
References 24 publications
3
120
0
2
Order By: Relevance
“…A similar study showed that cancer antigens could be detected at a concentration of 5 ng/ml (13). Detection of epidermal growth factor receptor and Her2 in a microarray format was achieved at 1 ng/ml levels using a sandwich assay and was increased to 0.1 ng/ml levels by direct labeling methods (7). Standard sandwich immunofluorescence assay was used to detect 75 different cytokines at a concentration of 1 ng/ml in a microarray format.…”
Section: Discussionmentioning
confidence: 99%
“…A similar study showed that cancer antigens could be detected at a concentration of 5 ng/ml (13). Detection of epidermal growth factor receptor and Her2 in a microarray format was achieved at 1 ng/ml levels using a sandwich assay and was increased to 0.1 ng/ml levels by direct labeling methods (7). Standard sandwich immunofluorescence assay was used to detect 75 different cytokines at a concentration of 1 ng/ml in a microarray format.…”
Section: Discussionmentioning
confidence: 99%
“…Nielsen et al (25) are developing microarrays to study signaling in networks of interacting proteins. Sandwich assays were developed to measure both the abundances and phosphorylation states of ErbB2, epidermal growth factor receptor, and the transferrin receptor.…”
Section: Tissue and Cell Culture Studiesmentioning
confidence: 99%
“…For example, secondary antibodies used in sandwich assays may target either total proteins or the active phosphotyrosine forms. This has been applied to breast cancer cell lysates to evaluate the activation of ERBB receptors upon ligand binding and after specific perturbation by receptor inhibitors (55).…”
Section: Protein Microarraysmentioning
confidence: 99%